Relationship of direct and estimated oxygen consumption in the intermittent resistance Yo-Yo test in female professional soccer players - Cofré-Bolados, Cristian; Rosemblat, Marcelo; Barriga-González, Diego; Farias-Valenzuela, Claudio; Espoz-Lazo, Sebastián; Segales-Gill, Dulce (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
In professional women's soccer there has been significant growth in recent decades, game analysis determines that distances between 8.5 and 10.3 km are covered, defining power and aerobic capacity as determining factors in the conditional physical profile of the players. The evaluation of aerobic power through maximum oxygen consumption (VO2max) is essential. The objective of this study was to compare the aerobic power determined by the Yo-Yo intermittent resistance test measured directly with a gas and metabolite analyzer v/s the calculation proposed by the Bansgbo estimation formula. The study methodology consisted in the evaluation of the Yo-Yo intermittent resistance test on the soccer field in 25 professional soccer players. The results of the study gave direct average relative values ​​of 42.53 ml/kg-min and estimated VO2max of 41.96 ml/kg-min, without significant differences (p= 0.22). It is concluded that the Yo-Yo test and the Bansgbo formula are relevant for the estimation of aerobic power in professional Chilean soccer players.